Assessing Our Work on Impact Evaluation - Goldstein, Markus; Skoufias, Emmanuel; Fiszbein, Ariel (World Bank, Washington, DC, 2012)
Over the last several years, the World Bank has increasingly engaged in impact evaluations as means of building evidence for results. During this process, the Bank has also produced an extensive variety of knowledge products. However, there are several institutional and resource issues that constrain the effectiveness of our impact evaluation work. This brief outlines recent gains in the Bank's work on impact evaluation, highlights several issues, and proposes some options to continue improving and expanding the Bank's efforts in this area.